Penguatan Literasi Informasi pada Pembelajaran Menulis Teks Eksplanasi melalui Media Pembelajaran Berbantuan Teknologi - Nelita Indah Islami; Andoyo Sastromiharjo; Khaerudin Kurniawan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The purpose of this article is to review the important role of technology-assisted learning media in improving students' information literacy which in this context is in learning to write explanatory texts. The approach used in this research is a literature review. A literature review is a way to assess and critically examine a body of knowledge, concepts, or findings from various previously written sources or findings from previously written sources. The results and discussion in this article contain four discussions that centrally discuss the use of technology-assisted learning media in improving information literacy in learning to write explanatory texts. The conclusion resulting from this research is that the use of technology-assisted media can be used as a learning media innovation and can have a positive influence in improving information literacy in terms of improving the ability to access information and evaluate the quality of information.